MCT1 in Invasive Ductal Carcinoma: Monocarboxylate Metabolism and Aggressive Breast Cancer - Johnson, Jennifer M.; Cotzia, Paolo; Fratamico, Roberto; Mikkilineni, Lekha; Chen, Jason; Colombo, Daniele; Mollaee, Mehri; Whitaker-Menezes, Diana; Domingo-Vidal, Marina; Lin, Zhao; Zhan, Tingting; Tuluc, Madalina; et al. (Frontiers in Cell and Developmental Biology, 2017)
Introduction: Monocarboxylate transporter 1 (MCT1) is an importer of monocarboxylates such as lactate and pyruvate and a marker of mitochondrial metabolism. MCT1 is highly expressed in a subgroup of cancer cells to allow for catabolite uptake from the tumor microenvironment to support mitochondrial metabolism. We studied the protein expression of MCT1 in a broad group of breast invasive ductal carcinoma specimens to determine its association with breast cancer subtypes and outcomes. Methods: MCT1 expression was evaluated by immunohistochemistry on tissue micro-arrays (TMA) obtained through our tumor bank. 257 cases were analyzed: 180 cases were estrogen receptor and/or progesterone receptor positive (ER+ and/or PR+), 62 cases were human epidermal growth factor receptor 2 positive (HER2+) and 56 cases were triple negative breast cancers (TNBC). MCT1 expression was quantified by digital pathology with Aperio software. The intensity of the staining was measured on a continuous scale (0-black to 255-bright white) using a co-localization algorithm. Statistical analysis was performed using a linear mixed model. Results: High MCT1 expression was more commonly found in TNBC compared to ER+ and/or PR+ and compared to HER-2+ (p < 0.001). Tumors with an in-situ component were less likely to stain strongly for MCT1 (p<0.05). High nuclear grade was associated with higher MCT1 staining (p<0.01). Higher T stage tumors were noted to have a higher expression of MCT1 (p<0.05). High MCT1 staining in cancer cells was associated with shorter progression free survival, increased risk of recurrence and larger size independent of TNBC status (p<0.05). Conclusion: MCT1 expression, which is a marker of high catabolite uptake and mitochondrial metabolism, is associated with recurrence in breast invasive ductal carcinoma. MCT1 expression as quantified with digital image analysis may be useful as a prognostic biomarker and to design clinical trials using MCT1 inhibitors.